Kinetics and predictive value of HBcrAg, HBV RNA and anti‐HBc during bulevirtide treatment of chronic HDV‐infected patients. Issue 4 (23rd January 2023) - Sandmann, Lisa; Deterding, Katja; Bremer, Birgit; Port, Kerstin; Cornberg, Markus; Wedemeyer, Heiner; Maasoumy, Benjamin
Abstract: The entry inhibitor bulevirtide (BLV) is a new treatment option for patients with chronic hepatitis D virus (HDV) infection and compensated liver disease. The aim of this study was to investigate the kinetic and predictive value of markers reflecting HBV cccDNA transcriptional activity and host immune response activity during BLV treatment in a real‐life cohort of HDV infected patients. Levels of HDV RNA, HBV RNA, hepatitis B core related antigen (HBcrAg) and hepatitis B core antibodies (anti‐HBc) were measured in 16 patients before (BL), after three (3M) and six (6M) months of treatment with BLV. All patients received nucleos(t)ide analogue treatment. HDV RNA declined in all patients during treatment. 38% (6/16) showed ≥ 2 log HDV RNA decline from BL to 6M and 11 patients (69%) normalized ALT levels. HBV RNA levels were low and only detectable in two to four patients. HBcrAg levels declined in 75% (12/16) of patients. Median HBcrAg levels declined significantly from BL to 6M (3.75 logU/ml (IQR 2.93‐4.78) vs. 3.4 logU/ml (IQR 2‐4.68), p=0.002). A similar trend was shown for anti‐HBc between BL and 6M. Levels of HBcrAg or anti‐HBc did not differ significantly between patients with or without ≥ 2 log HDV RNA decline from BL to 6M.After 6 months treatment with BLV, levels of HBcrAg showed a significant decline, while HBV RNA and anti‐HBc levels did not change. Reduction of HBV cccDNA transcriptional activity and immunological effects of antiviral treatment might explain these changes.